2008
DOI: 10.1210/me.2007-0274
|View full text |Cite
|
Sign up to set email alerts
|

Altered Selectivity of Parathyroid Hormone (PTH) and PTH-Related Protein (PTHrP) for Distinct Conformations of the PTH/PTHrP Receptor

Abstract: PTH and PTHrP use the same G protein-coupled receptor, the PTH/PTHrP receptor (PTHR), to mediate their distinct biological actions. The extent to which the mechanisms by which the two ligands bind to the PTHR differ is unclear. We examined this question using several pharmacological and biophysical approaches. Kinetic dissociation and equilibrium binding assays revealed that the binding of [(125)I]PTHrP(1-36) to the PTHR was more sensitive to GTPgammaS (added to functionally uncouple PTHR-G protein complexes) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
205
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(220 citation statements)
references
References 38 publications
14
205
0
1
Order By: Relevance
“…The biological actions of PTH1R apparently involved in longevity (as well as in growth plate and tooth eruption) most likely reside in local actions of the N terminus of PTHrP rather than in circulating PTH, in view of the fact that Pth null mice do not exhibit a reduced life span (23) and PTH levels were normal in our model. These distinct actions of the Nterminal domains of PTH and PTHrP may reflect conformational selectivity for the PTH1R, as recently described (46).…”
Section: Discussionsupporting
confidence: 58%
“…The biological actions of PTH1R apparently involved in longevity (as well as in growth plate and tooth eruption) most likely reside in local actions of the N terminus of PTHrP rather than in circulating PTH, in view of the fact that Pth null mice do not exhibit a reduced life span (23) and PTH levels were normal in our model. These distinct actions of the Nterminal domains of PTH and PTHrP may reflect conformational selectivity for the PTH1R, as recently described (46).…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, a recent report has shown that transient (1 h) but not continuous exposure of human MSCs to 50 nM PTH inhibited their differentiation to adipocytes (Rickard et al, 2006). The finding that a short exposure to the latter peptide was as efficient as the continuous presence of PTHrP , as shown here, to inhibit adipogenesis in these cells might be related to their different capacity to bind stably to different conformations of the PTH1R (Dean et al, 2008); considering that both peptides are likely to act through the PTH1R in human MSCs. Related to these in vitro data, a decrease in the expression of adipogenic genes in bone were found in osteopenic rats after daily administration of PTH (1-34) (Kulkarni et al, 2007).…”
Section: Discussionsupporting
confidence: 66%
“…For these assays, Gβγ CFP was expressed in HEK293 cells stably expressing HA-tagged PTHR (HA-PTHR), and cell lysates were prepared at different time points after a short exposure to either M-PTH(1-28) or M-PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), modified analogs of PTH that induce longer or shorter cAMP generation and biological responses, respectively (20). The difference in duration of cAMP signaling is thought to depend on the capacity of M-PTH(1-28), like PTH , to form an unusually persistent high-affinity complex with PTHR that is independent of G-protein coupling, whereas M-PTH(1-14) forms a more conventional high-affinity complex that is transient and dependent on G-protein coupling (2,20,21). The interactions of HA-PTHR with Gβγ CFP and β-arrestins, weakly detectable under basal conditions, increased significantly within 5 min after challenge with M-PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) or M-PTH(1-28) (Fig.…”
Section: Resultsmentioning
confidence: 99%